Community Compliance and Usage of Insecticide-Treated Nets (ITNs) for Malaria Prevention in the Upper River Region of The Gambia - Babucarr Jassey; Ririh Yudhastuti; Heny Arwati; Lamin Ceesay; Ebrima Jatta; Yankuba Fabureh; Baba Ceesay; Omar Jallow; Samuel S Gomez; Ousman F Bojang; Alfusainey Manneh; Khuliyah Chandraning Diyannah (Health Dynamics, 2026)
Malaria remains a major public health threat in sub-Saharan Africa, and the consistent use of insecticide-treated nets (ITNs) is a proven strategy for reducing transmission by reducing human-vector or physical contact. While distribution efforts have increased access and coverage, actual household utilization often lags behind ownership. This study evaluated ITN usage patterns and community compliance in the Upper River Region (URR) of The Gambia to better understand the gap between possessing a net and using it correctly. A community-based study was conducted across several districts in the URR, including Sandu, Jimara, Wulli East, Wulli West, Basse (Fulladu East), Tumana, and Kantora. Using a Community Compliance Index (CCI) framework, data were collected from 1,000 households through interviewer-administered questionnaires and direct environmental observations. The study assessed self-reported nightly net use, knowledge of ITN benefits, and observed physical conditions of nets, such as whether they were properly hung and tucked. Survey data revealed high levels of net ownership, with many respondents reporting that their households have enough nets for everyone. While a strong majority of participants acknowledged that sleeping under a net helps prevent malaria, barriers to consistent use remain. Common challenges identified by the community include discomfort due to nighttime heat and overcrowded sleeping areas. Direct observations in several households also highlighted a need for better net maintenance, as some nets were found to be in poor condition or not properly mounted over sleeping areas. Despite successful distribution and high community awareness of ITN benefits in the URR, actual nightly utilization is influenced by environmental discomfort and household structural limitations. To move toward malaria pre-elimination, MoH/NMCP Gambia should go beyond simple distribution and focus on behavioral change interventions. Strategies should include local demonstrations on proper net hanging and repair, as well as community-led initiatives to address seasonal discomfort during the peak transmission period